The mixed blessing of IMF intervention: Signalling versus liquidity support - Zwart, Sanne (Journal of Financial Stability, 2007)
Although IMF support is supposed to benefit a country, it might be bad news that the IMF believes intervention is necessary. This paper analyzes a bank run model in which both the liquidity effect and the signalling effect of the intervention occur. The IMF strategically provides liquidity support to facilitate market functioning. When the IMF intervenes and has large resources, it uses the signalling to aim for a “half run” and off-sets the negative consequences with the liquidity support. For small IMF resources, the negative signalling effect might not be off-set and the IMF presence can be distorting.